THE INFLUENCE OF FASHION TRENDS, CELEBRITY ENDORSEMENTS AND CUSTOMER REVIEWS ON THE DECISION TO REPEAT ORDER TIKTOK SHOP PRODUCTS : (CASE STUDY ON STUDENTS OF PGRI WIRANEGARA UNIVERSITY) - Aini, Karina Nur; Indarti, Nunuk; Sangadji, Etta Mamang (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
TikTok shop is one of the e-commerce provided by the TikTok application. TikTok shop provides a platform for business people to promote the products they sell. Therefore, it is necessary to increase repeat order decisions which are supported by developments in fashion trends, the use of celebrities as endorsers and customer reviews as material for consideration This research aims to determine the influence of fashion trends (X1), celebrity endorsements (X2), and customer reviews (X3) on the decision to repeat orders for TikTok shop products among PGRI Wiranegara University students, both partially and simultaneously. The method used in this research is a quantitative research method with a purposive sampling technique. the sample used in this study was 65 respondens data collection uses observation and distributing questionnaires to PGRI Wiranegara University students who carry out repeat orders and other literacy reviews. Then the results were analyzed using multiple linear regression analysis. The research results concluded that fashion trends had a positive and partially insignificant effect on repeat order decisions because the sig value. 0.342 > 0.05. Celebrity endorsements have a partially positive and significant effect on repeat order decisions because of the sig value. 0.016 < 0.05. Because of the high value, customer reviews have a considerable and partly beneficial impact on decisions to place repeat orders. 0.000 < 0.05. Because the F-count > F-Table value is 42.253 > 2.755, fashion trends, celebrity endorsements, and customer reviews all have a positive and significant impact on PGRI Wiranegara University students' decisions to repurchase things from the TikTok shop. The coefficient of determination for the adjusted R square is 0.659. This indicates that Fashion Trends (X1), Celebrity Endorsements (X2), and Customer Reviews (X3) account for 65.9% of the Influence on the Repeat Order Decision (Y), with other variables not included in the research accounting for the remaining 34.1 Keywords: Celebrity Endorsement, Customer Reviews, Repeat Order Decisions, and Fashion Trends